THE LEVEL OF STRESS AMONG THE PARENTS OF CHILDREN WITH LEARNING DISABILITIES (LD) IN MALAYSIA (Proceedings of International Conference on Special Education, 2015)
The main purpose of this study is to investigate the level of stress among the parents of children with learning disabilities (LD) attending the inclusive program in Malaysian primary schools. The data were solicited from Parental Stress Scale – a self report scale which involved 66 parents from in the district of Batang Padang in the state of Perak. The results showed that a total of 21 (19.1%) parents experiencing stress at low level and they are in the state of normal. Whilst 80 (72.7%) of the parents were suffering average level of stress (a score of 14 to 19) which is considered as mild. Furthermore, the analysis also showed that only 9 (8.2%) of them experienced high level of stress which is classified as severe. The findings have shown that parents of girl with disabilities was associated with higher stress. Parents engaged in more lucrative and prestigious occupations had more stress than parents engaged in less prestigious and lucrative occupations irrespective of their income. The findings also show there is no significant different in term of stress between the different ethnic groups (Malays, Chinese and Indian) and religious group (Muslims, Christians, Buddhists and Hindus) in Malaysia. Furthermore, religion was found to be a common coping resource used by the parents. This study implies that there are critical roles for parents in coping their emotional stress. Apart from this, all parties especially the government agencies such Special Education Department, Department of Social Welfare and etc should formulate programs to help the parents by providing services such counselling, interpersonal skills and early intervention